THE MAIN PRIORITIES OF RUSSIAN EDUCATION IN THE XXI CENTURY IN THE CONDITIONS OF MARKET ECONOMY - Irina M. Kornilova (Статистика и экономика, 2016)
This article deals with the problem of education, which is closely related to the goals of society and is a decisive factor in its development. Establishment and continuous improvement of market relations in Russia, democratization of public life, the emergence of various forms of ownership have created a competitive environment in both the manufacturing and non-manufacturing areas.The educational sphere is no exception, and is adapted to the new operating conditions, the acquisition of new forms in their perfection. The result is a previously unknown educational structures that differ from the previous merger of several forms of ownership association differ in their targeting of the organization, dependent both on market conditions as well as from the budget of public spending.